Shakespeare and the theater - Shuter, Jane (Chicago, Illinois Capstone Heinemann Library, 2014)
Did you know that the only known purpose-built theaters in Shakespeare's England were in London and Bristol? Or that only boys and men could become actors? This fascinating book outlines the world of the theater in which William Shakespeare wrote and did business, from outdoor and indoor theaters, the life of an actor, and touring, to how plays were written, funded, and staged
A gift from book Africa
Plays
1 2 13
NEW_ZTN_GN
Keywords: Shakespeare, William -- 1564-1616 -- Stage history -- To 1625; Shakespeare, William -- 1564-1616; Theater -- England -- History -- 16th century